The Influence of Removable Complete Denture on Pro‐Oxidant Antioxidant Balance and Redox‐Sensitive Inflammation Biomarker NF‐ĸB in the Oral Cavity: An Interventional Follow‐Up Study - Mirjana Bošković; Dušan Sokolović; Saša Stanković; Ivan Ristić; Jordan Popović; Gordana Kocić (Wiley, 2024)
ABSTRACT Objectives Oxidative stress, an imbalance between the body's natural antioxidant defenses and the production of reactive oxygen species (ROS), can result in serious oral diseases, including oral cancer, periodontal diseases, and oral lichen planus, through the activation of the redox‐sensitive transcription factors and inflammation. The purpose of this study was to assess the potential effects of a removable complete denture on the levels of oxidative stress markers, such as lipid peroxidation (MDA), advanced oxidation protein products (AOPP), and catalase, and the quantitative expression of the redox‐sensitive transcription factor NF‐κB p65 subunit. Materials and Methods This interventional follow‐up study enrolled 40 participants of both sexes aged 28-78 years, with a median age of 56 years, where unstimulated saliva was collected before denture placement, immediately after the denture placement, and 24 h, 7 days, and 30 days after the denture placement. The most prominent ROS overproduction was reported on the seventh day (p < 0.05), followed by a significant fall in antioxidative defense. Results The NF‐κB p65 subunit, whose expression pattern was highest in the same time period on the seventh day, serves as a signaling molecule for redox imbalance due to ROS production. Over the next 30 days, its levels remained moderately increased compared to the basal value, which may influence pro‐inflammatory pathways and the integrity of oral tissue components. These alterations may be induced by the dentures, which can produce high pressures on the supporting tissues or by the synthetic materials used for producing the dentures. Conclusion Our research may help to clarify the potential pathways by which oxidative stress and redox‐sensitive inflammatory mediators, as well as mechanical and chemical irritants, may serve as risk factors for premalignant lesions in the mouth. Further research on this topic is required to understand the molecular mechanisms behind the relationship between inflammation and oral premalignant lesions caused by mechanical and chemical irritation.